Strategy of Management of Village-Owned Enterprises (Bumdes) Batu Bini, Padang Batung District, Hulu Sungai Selatan Regency - Yusril, Yusril; Indahwati, Rini; Pasaribu, Fajar (Sumber Belajar Sejahtera, 2025)
Villages, with all their natural and human potential, play an important role in increasing national income. Therefore, development must be directed at the sustainable use of resources in rural areas. The New Generation BUMDes is part of the process of utilizing existing resources. This study aims to (1) identify the obstacles faced in managing the New Generation BUMDes and (2) formulate a management strategy for the New Generation BUMDes in Batu Bini Village, Padang Batung District. This study uses a qualitative descriptive approach, with the research subject being the New Generation BUMDes in Batu Bini Village, South Hulu Sungai Regency. The study results show that: (1) there are still several obstacles in BUMDes management, including budget constraints, insufficient capacity of human resources among managers, and a lack of participation from the community and private sector. (2) The management strategy of the New Generation BUMDes is carried out based on applicable regulations, including the process of institutional formation and the provision of facilities and infrastructure, as well as managing BUMDes with the continued use of the Village Government Budget. The study concludes that the management of the New Generation BUMDes in Batu Bini Village has been carried out in accordance with the applicable regulations. However, challenges such as limited budgets, inadequate human resource capacity, and minimal participation from the community and private sector must be addressed to ensure more effective BUMDes management, ultimately achieving the goals of its establishment.